2010
DOI: 10.1161/atvbaha.110.216143
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Levels of Soluble CD40 Ligand Exacerbate Platelet Aggregation and Thrombus Formation Through a CD40-Dependent Tumor Necrosis Factor Receptor–Associated Factor-2/Rac1/p38 Mitogen-Activated Protein Kinase Signaling Pathway

Abstract: Objective-CD40 ligand is a thromboinflammatory molecule that predicts cardiovascular events. Platelets constitute the major source of soluble CD40 ligand (sCD40L), which has been shown to influence platelet activation, although its exact functional impact on platelets and the underlying mechanisms remain undefined. We aimed to determine the impact and the signaling mechanisms of sCD40L on platelets. Methods and Results-sCD40L strongly enhances platelet activation and aggregation. Human platelets treated with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 37 publications
3
69
0
1
Order By: Relevance
“…Scientists have since analyzed the cause for the pathophysiological problems identified clinically. Their reports help to identify platelets as a source for soluble CD154 or CD40 ligand and demonstrate a correlation between increased circulating levels of this molecule and increased thrombus formation (Yacoub et al, 2010, Yuan et al, 2010. These studies show further that CD154's concentration is increased in hypertensive patients included non-diabetic and pre-diabetic persons with metabolic syndrome (Unek et al, 2010).…”
Section: Interfering With Cd40/cd154 Ligationmentioning
confidence: 85%
“…Scientists have since analyzed the cause for the pathophysiological problems identified clinically. Their reports help to identify platelets as a source for soluble CD154 or CD40 ligand and demonstrate a correlation between increased circulating levels of this molecule and increased thrombus formation (Yacoub et al, 2010, Yuan et al, 2010. These studies show further that CD154's concentration is increased in hypertensive patients included non-diabetic and pre-diabetic persons with metabolic syndrome (Unek et al, 2010).…”
Section: Interfering With Cd40/cd154 Ligationmentioning
confidence: 85%
“…The clinical development of the corresponding biological (humanized monoclonal anti-CD154) antibodies, however was previously thwarted by serious thromboembolic complications (Kawai et al, 2000;Koyama et al, 2004), which are suspected to have been caused by an interference with the stabilizing effect of soluble CD154 on freshly formed thrombi (Andre et al, 2002). In fact, the main source of soluble CD154 are aggregating platelets from which the membrane-bound CD154 is shed upon activation (Kaya et al, 2011;Pamukcu et al, 2011;Silvain et al, 2011;Yacoub et al, 2010). More recently, however, some progress has been made towards the development of monoclonal antibodies with less side effects (Hussein et al, 2010).…”
Section: An Important Cytokine That Is Produced By Activated T-helpermentioning
confidence: 99%
“…16 In addition, it has been demonstrated that upon CD40L binding CD40 activation on platelets can enhance platelet function and promote the secretion of inflammatory cytokines involved in plaque formation (this aspect will be discussed in greater detail bellow). [27][28][29] …”
Section: Cd40mentioning
confidence: 99%